2012
DOI: 10.3892/ijmm.2012.1143
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of changes in protein expression in serum from animals exposed to paraquat

Abstract: Abstract. Paraquat (PQ) poisoning remains a major public health concern in many countries. Extensive research has focused on finding early diagnostic biomarkers of acute PQ poisoning. In order to investigate the characterization of diagnostic biomarkers in PQ poisoning, we utilized proteomic analysis using serum from rats exposed to PQ, and we identified 8 differentially expressed proteins from over 500 protein spots. The expression of apolipoprotein E (ApoE), preprohaptoglobin (Pphg), a precursor of haptoglob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
2
1
Order By: Relevance
“…However, our work presented that NADH dehydrogenase (ubiquinone) iron-sulfur protein 8, which is related to electron transport, was found to be down-regulated in the treatment sample ( Supplemental data Table 4 ). It is noteworthy that Kim et al [ 24 ] reported great induction of ApoE, Pphg, Hp and C3 proteins and dramatic reduction of FGG and Ac-158 in sera upon PQ exposure, which, however, were not detected in the lung tissues in the present study ( Supplementary data Table 5 ).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…However, our work presented that NADH dehydrogenase (ubiquinone) iron-sulfur protein 8, which is related to electron transport, was found to be down-regulated in the treatment sample ( Supplemental data Table 4 ). It is noteworthy that Kim et al [ 24 ] reported great induction of ApoE, Pphg, Hp and C3 proteins and dramatic reduction of FGG and Ac-158 in sera upon PQ exposure, which, however, were not detected in the lung tissues in the present study ( Supplementary data Table 5 ).…”
Section: Discussioncontrasting
confidence: 53%
“…Early diagnostic biomarkers are important for treatment of acute PQ poisoning. In order to investigate the characterization of diagnostic biomarkers in PQ poisoning, Kim et al [ 24 ] employed a 2D-PAGE MALDI-TOF/TOF approach and identified that apolipoprotein E (ApoE), a precursor of haptoglobin (Hp) and fibrinogen γ-chain (FGG) were potential biomarkers of PQ exposure in rat sera. In an effort to develop a remedy for PQ poisoning, Kim et al [ 25 ] conducted proteomic analysis of PQ-poisoned male CD(SD)IGS rat lungs to identify any protective effects of acai berry on the PQ poisoning.…”
Section: Introductionmentioning
confidence: 99%
“…These persistent lipophilic compounds could accumulate in the retina and increase oxidative stress in response to light exposure. Potentially of great importance to AMD are observations that complement pathways can be activated by some pesticides, including DDT ( Dutta et al 2008 ), other organochlorine insecticides ( Kumar et al 2014 ), malathion ( Ayub et al 2001 ), the pyrethroid fenvalerate ( Dutta and Das 2011 ), and paraquat ( Kim YS et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%